Timbalier Island Restoration - Anderson, Sean (California State University Channel Islands Library)
Timbailer Island is facing serious erosion problems from storm-generated winds and waves. Tropical storms and hurricanes have caused breaches in severeal places on the island as well as erosion and loss of much of the island's sand.